L’architettura trascendentale della metapsicologia freudiana (Parte seconda) - Guma, Francesca (Metapsychologica - rivista di psicanalisi freudiana, 2023)
Metapsychology doesn’t only emerge from a transcendental perspective, but it develops internally bringing with it profound enrichment. In this second part of the article it is shown how Freud finds the Übergang is able to connect psychoanalytic science to the empirical aspect of psychical phenomena. His exquisite Kantian pace allows him to not only lay solid epistemological foundations for his discipline, but also to provide an objective description of the psyche and a naturalisation of the cogito. If the last Kant has assured the objectivity of physics, Freud, overcoming the fourth paralogism of Pure Reason and taking into account the finality of living beings, continues in his specific field demonstrating that psychology, appropriately developed, is a natural science.